Museological Management: Performance Paradigms, Results and Perspectives: The panorama of the Portuguese Museum Network fifteen years after its creation (Cadernos de Sociomuseologia, 2020)
Humberto Filipe Simões RendeiroDepartamento de Museologia, Universidade Lusófona de Humanidades e Tecnologias.Tese de Doutoramento -PhD (2019)Abstract The first survey of the Portuguese museum’s reality was outlined in 1998, materializing in 2000 in the edition of the Enquiry of Museums in Portugal, a work that layed the basis of the Portuguese Network of Museums (RPM) and which, due to the results it brought to the public on the national museum panorama, served as basis of the present investigation, which seeks to update the current situation of RPM museums. Later, in 2004, the Portuguese Museums’ Frame-Law was enacted. This document determines the legal regime common to Portuguese museums and establishes the principles of national museum policy. It is also from this legal act that the performance of the functions of museums, which are the basis of this investigation, is identified and established, since it is from them that one can infer the performance of Portuguese museums. Thus, based on the museums inscribed in the RPM, the theoretical foundations of what one can consider to be a museum were identified, with reference to the mentioned documents and, also, the ICOM Code of Ethics for Museums. An analysis was made of the performance of RPM museums in relation to the four basic museum functions of a museum mission, based on an inquiry addressed to them. The museum functions considered are research, incorporation, conservation and communication. Finally, in a comparative perspective, we tried to draw the national museum’s panorama distinguishing between what is theoretically stipulated and what happens in practice. Since museums enrolled in RPM (i) have undergone a certification process to integrate them in the network, (ii) are covered by the Portuguese Museums’ Frame-Law, and (iii) are covered by the ICOM Code of Conduct for Museums, where standards for better professional performance are established; it can be assumed that these museums are in Portugal better placed to carry out their mission. Their diagnosis is representative of the best practices in the field in our country (or not so much); this is the premise on which the investigation began. The survey, composed of sixty-six questions, allows us to conclude that what is established in theory about national museum policies is not mirrored in practical terms; that financial / budgetary deficiencies are one of the main problems of Portuguese museums; the performance of museum functions is not homogeneous when compared among the various governing bodies; and that there is fundamental work to be done as regards communication. Keywords: Museum Functions; Museum Management; Museums; Museology; Portuguese Museum’s Network.